Mineral economies— Indebtedness without growth - Susanne Schattner (Intereconomics, 1982)
Developing countries with considerable mineral reserves might be expected to have fewer problems with debt-servicing than other developing countries lacking these resources. In fact, during the past decade a not insignificant number of the former had to apply for a rescheduling of their foreign debts. What are the reasons behind this unexpected development?
Keywords: 330; International Indebtedness